Postharvest quality maintenance of 'Royal Gala' and 'Galaxy' apples stored under controlled atmosphere Manutenção da qualidade pós-colheita de maçãs 'Royal Gala' e 'Galaxy' sob armazenamento em atmosfera controlada - Brackmann A. (2008)
The aim of this research was to evaluate the efficiency of controlled atmosphere conditions in the conservation of 'Royal Gala' and 'Galaxy' apples. The experimental design was completely randomized, with four replicates and the experimental unit composed by 25 fruits. Treatments were originated from the combination of two cultivars (Royal Gala and Galaxy) and seven storage conditions, that were: [1] Cold storage (CS); [2] controlled atmosphere (CA) 1.0kPa O2 + 2.0kPa CO2; [3] 1.0kPa O2 + 2.5kPa CO2; [4] 1.0kPa O2 + 3.0kPa CO2; [5] 0.8kPa O2 + 2.5kPa CO2; [6] 1.2kPa O2 + 2.5kPa CO 2 and [7] 1.0kPa O2 + 2.5kPa CO2. The storage temperature in the treatments 1 to 6 were +0.5°C and treatment 7, -0.5°C. Fruit quality was evaluated after 8 months of storage and 7 days at 20°C. 'Galaxy' apple showed lower decay percentage, less mealy fruits and higher firmness in relation to 'Royal Gala' apples and there was no interaction between these parameters and storage conditions. 'Galaxy' apples showed lower percentage of internal breakdown and higher titratable acidity when compared with 'Royal Gala' apples. The best CA storage condition for 'Royal Gala' apples was 1.0kPa O2 + 2.5kPa CO2 and for 'Galaxy' apples, 0.8 to 1.0kPa O2 and 2.5kPa CO2. 'Galaxy' apple can be stored during a larger period, because it presents a superior storage potential in relation to 'Royal Gala' apples.